Comet assay to measure DNA repair: approach and applications - Azqueta, Amaya; Slyskova, Jana; Langie, Sabine A. S.; O’Neill Gaivão, Isabel; Collins, Andrew (Frontiers in Genetics, 2014)
Cellular repair enzymes remove virtually all DNA damage before it is fixed; repair therefore plays a crucial role in preventing cancer. Repair studied at the level of transcription correlates poorly with enzyme activity, and so assays of phenotype are needed. In a biochemical approach, substrate nucleoids containing specific DNA lesions are incubated with cell extract; repair enzymes in the extract induce breaks at damage sites and the breaks are measured with the comet assay. The nature of the substrate lesions defines the repair pathway to be studied. This in vitro DNA repair assay has been modified for use in animal tissues, specifically to study the effects of aging and nutritional intervention on repair. Recently, the assay was applied to different strains of Drosophila melanogaster proficient and deficient in DNA repair. Most applications of the repair assay have been in human biomonitoring. Individual DNA repair activity may be a marker of cancer susceptibility; alternatively, high repair activity may result from induction of repair enzymes by exposure to DNA-damaging agents. Studies to date have examined effects of environment, nutrition, lifestyle and occupation, in addition to clinical investigations.